Concurrent Consideration of Technical and Human Aspects in Security Requirements Engineering - Fujs, Damjan (Informatica, 2024)
This article is an extended abstract of the doctoral dissertation entitled “Tailoring security-related software and training requirements to users based on their categorization” (Fujs, 2024). Security has traditionally been ensured by technical solutions in the concluding stages of software development. The fact that security is considered an additional function means that a vulnerability is fixed with security patches as soon as it occurs. However, the importance of human factors is increasingly being recognized, as technical solutions alone are not enough to close security gaps. In order to address this shortcoming, we proposed an approach that simultaneously addresses technical as well as human aspects - already in the initial stages of software development.